2005
DOI: 10.1007/s10162-004-5021-6
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain Induces Apoptotic Cell Death in Type I Spiral Ganglion Neurons, but not Type II Neurons

Abstract: Application of ouabain to the intact round-window (RW) membrane of the gerbil cochlea induces apoptosis in most spiral ganglion neurons (SGNs), leaving a few neurons intact (Schmiedt et al. 2002). Here, physiological measures and immunostaining were used to examine the process of SGN degeneration at 3, 6, 12, and 24 h, 4 days, and 1 and 5 months after ouabain treatment. The few remaining neurons surviving up to 5 months after ouabain treatment were immunoreactive for peripherin, a type II neuron marker. Periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
99
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(111 citation statements)
references
References 53 publications
(46 reference statements)
12
99
0
Order By: Relevance
“…Specifically, these experiments show threshold increases or complete abolishment of the compound action potential without a reduction of the endocochlear potential (Schmiedt et al 2002;Wang et al 2006). Moreover, chronic exposure to ouabain is associated with degeneration of type I but not type II SGNs in the gerbil cochlea (Lang et al 2005). These findings are consistent with our observation of the NKAα3 in type I but not type II spiral ganglion afferent terminals.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, these experiments show threshold increases or complete abolishment of the compound action potential without a reduction of the endocochlear potential (Schmiedt et al 2002;Wang et al 2006). Moreover, chronic exposure to ouabain is associated with degeneration of type I but not type II SGNs in the gerbil cochlea (Lang et al 2005). These findings are consistent with our observation of the NKAα3 in type I but not type II spiral ganglion afferent terminals.…”
Section: Discussionsupporting
confidence: 92%
“…Our previous studies have shown that application of ouabain to the RW niche of the gerbil inner ear results in degeneration of most SGNs without cell losses within the organ of Corti and cochlear lateral wall Lang et al 2005). In this model, a series of apoptotic events, including a redistribution of cytochrome c and poly (ADP-ribose) polymerase and activation of caspase 3, occurs in most ganglion cells within 2 days (Lang et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…In this model, a series of apoptotic events, including a redistribution of cytochrome c and poly (ADP-ribose) polymerase and activation of caspase 3, occurs in most ganglion cells within 2 days (Lang et al 2005). Most spiral ganglion cells along with their peripheral and central processes were absent 1 week after ouabain exposure .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations